Macroeconomic dynamics in low income economies - Bangara, Bertha Chipo (School of Economics, 2016)
This thesis investigates the dynamic effects of two interrelated characteristics of low income economies: Commodity concentration of exports, and foreign exchange constraints on the behaviour of key macroeconomic variables. The literature defines the problem of export fluctuations with reference to commodity concentration of exports, the ability to forecast the fluctuations, and the availability of foreign reserves to meet the effects of fluctuations. When a country's exports are concentrated in a single commodity or a few commodities, price fluctuations may lead to low export earnings and low reserves. This has implications for the macroeconomic environment, since low levels of reserves may not adequately mitigate the effects of price fluctuations. Therefore, we first explore the macroeconomic effects of price fluctuations in low income economies with a high commodity concentration of exports. Specifically, we examine the dynamic response of selected macroeconomic variables to tobacco price shocks in Malawi, using quarterly time series data from 1980 to 2012. Using innovation accounting in a structural vector auto regressive (SVAR) model with short-run restrictions, we find that a positive tobacco price shock increases gross domestic product (GDP), reduces consumer prices, and induces an appreciation of the real exchange rate. These results are also robust to SVAR in differenced data and co-integrating vector autoregressive (CVAR) models. The CVAR confirms the existence of a long run-relationship among the variables, with causality running from tobacco prices to the three variables. Second, we provide an empirical analysis of the effect of shortage of foreign exchange in an import dependent, low income economy. It has become clear from the existing literature that low income economies tend to suffer from foreign exchange shortages exacerbated by their exports. Because of the concentration of their exports, these countries are susceptible to international price fluctuations which affect the level of foreign exchange. In addition, these countries tend to overvalue and fix their exchange rate, which worsens their terms of trade and leads to low levels of reserves. This causes foreign exchange shortages and leads to excess demand for foreign exchange by importers. We therefore investigate the implications of foreign exchange constraints on the dynamic behaviour of key macroeconomic variables in low income, import dependent economies.